Striated Nephrogram as an Incidental Finding in MRI Examination of Children - Strocka, S.; Sorge, I.; Ritter, L.; Hirsch, F. W. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: A highly striated contrast pattern of the kidneys occasionally appears in abdominal MRI examinations of children following the administration of gadolinium. As this phenomenon is well known but has not yet been explicitly described in literature, we investigated how frequently and in which clinical context this occurred.Material and Methods: 855 abdominal MRI examinations with contrast media of 362 children between 2006 and 2014 were analysed retrospectively.Results: A striated renal parenchyma was found in a total of nine children and eleven examinations (1.3 % of examinations) and did only occur at a field strength of 3 Tesla. Of these children, seven had previously had tumors and chemotherapy. In two children there was no evidence of a previously serious condition with medications or a kidney disease. All of them had a normal renal function.Conclusion: A noticeably striated nephrogram in the later phase of an MRI examination following administration of gadolinium may appear as an incidental finding in examinations at 3 Tesla without pathological relevance.Key points:• striated nephrograms may appear at a field strength of 3 Tesla.• incidental finding without pathological relevance.Citation Format:• Strocka S, Sorge I, Ritter L et al. Striated nephrogram as an incidental finding in MRI examination of children. Fortschr Röntgenstr 2016; 188: 69 – 72
Keywords: abdomen; MR-imaging; contrast agents